Pemetaan Jejak Karbon pada Sektor Energi dari Aktivitas Permukiman di Kota Bogor, Jawa Barat - Iren Chaerunnisa; Wilma Nurrul Adzillah; Azis Kemal Fauzie (Jurnal Serambi Engineering, 2024)
One of the causes of global warming is the presence of carbon emissions in the atmosphere. Carbon emissions trapped in the atmosphere will cause the Earth's average temperature to rise. Therefore, it is necessary to calculate and map carbon footprints to anticipate the effects of global warming, one of which is in the city of Bogor. The energy sector is the sector that contributes 43.83% compared to other sectors. The calculation of the carbon footprint is based on IPCC formulas. Meanwhile, data collection is carried out through the distribution of questionnaires and direct interviews with the residents of Bogor City in 6 sub-districts. The calculated carbon footprint of the energy sector comes from residential activities, namely the use of fuel for cooking, fuel oil for motor vehicles and electricity used during 1 month. The results of the energy sector carbon footprint in Bogor City were then mapped at different levels using QGIS. The calculation of CO_2 emissions in Bogor City resulted in 2,244,809.6 tons/year and was dominated by North Bogor District as the largest contributor of CO_2 emissions.